A synopsis of Polysphaeria (Rubiaceae) in Mozambique, including two new species - Darbyshire, Iain; Langa, Clayton; Romeiras, Maria M. (Phytotaxa, 2019)
The genus Polysphaeria is investigated in Mozambique based on detailed morphological studies of herbarium specimens, resulting in the recognition of two new species. The first, P. ribauensis, is based on Kraussia sp. A of Flora Zambesiaca and is endemic to the Ribáuè Mountains of Nampula Province. The second, P. harrisii, is known only from Mount Mabu and Mount Ile in Zambézia Province, and has previously been confused with P. lanceolata. The affinities of these two species are discussed and a synopsis of the genus in Mozambique is presented, including a key to the five species now recognised, and notes on the distribution, ecology and conservation status of each species.